PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS XI MIPA SMAN 1 2x11 ENAM LINGKUNG - Artika Mutiara Saima (Jurnal Edukasi dan Penelitian Matematika, 2022)
Learning outcomes can measure a students’s abilities. But in reality, there were still many math learning outcomes from poor or inadequate students. Discovery learning is one in every of learning models that could enhance college students mathematics studying outcomes. This type of research is a pre-experimental research using the One Group Pretest Posttest Design. The purpose of this study was to describe the development of mathematical learning outcomes of students in class XI IPA SMAN 1 2x11 Enam Lingkung after applying in the discovery learning model. The population of this study consisted of students in class XI MIPA SMAN 1 2x11 Enam Lingkung. The research subject being students of class XI MIPA 2. Pre-testing and post-testing of learning outcomes in the form of essay questions served as a research tool. Data were collected using tests and analyzed by paired sample t-tests and normalized gain tests. Research has shown that the average pre-test score for the experimental class is 50.37 and the average post-test score is 79.34. The results of the analysis came to the conclusion that the use of the discovery learning model influences the learning outcomes of mathematics. Keywords —Learning Outcome, Pre-Experiment, Discovery Learning